Psalții Dionisie Fotino și Petru Efesiu – ultimele glorii ale emigrației grecești în Țările Române - Militaru, Marius-Stelian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The study presents a parallel between the psaltes, composers and teachers Dionysios Photeinos (1777-1821) and Peter the Ephesian (ca. 1770/1774-1840), who were active in Wallachia at the beginning of the 19th century (the end of the Phanariot period and the first reign of an earthly ruler). Based on the scarce information provided by the sources, the study aims to place the activity of the two teachers, promoters of church music and the Chrysantic reform (in the case of Peter the Ephesian) within the historical and cultural frame of the era. The study considers the academic background of the two, their teaching activity in Wallachia and the existing continuity between Dionysios Photeinos and Peter the Ephesian, through disciples such as Anton Pann and Chesarie Căpăţână, bishop of Buzău, while also underlining some common traits concerning their culture, character, and the way they had adapted to the realities of their new homeland, where both these great psaltes passed away.